Preventing the medication errors in hospitals: A qualitative study - Alireza Salar; Fatemeh Kiani; Nasrin Rezaee (International Journal of Africa Nursing Sciences, 2020)
Background and purpose: Administering drugs is one of the primary nursing acts in hospital wards and medication errors are one of the worst errors among nurses leading to unpleasant results for patients. Thus, this study aimed to identify ways to prevent medication errors in the hospital wards in Iran. Materials and methods: This qualitative content analysis study was conducted on 16 nurses and 1 physician from 10 August 2019 to 30 March 2020. The participants were selected using a purposive sampling method. Data were collected using semi-structured interviews. Thematic analysis was used to extract key themes from the data. Results: The two themes extracted to prevent medication errors were “acting professional” and “presenting technical strategies”, respectively. Conclusion: Results showed that medication errors happen due to various reasons but if the nurses act professionally and the control systems like accreditation have a clearer role, both the medication errors and their prevention methods are discovered.